2001
DOI: 10.1097/00005768-200108000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Knee bracing after ACL reconstruction: effects on postural control and proprioception

Abstract: In general, bracing appears to improve performance during tasks characterized by relatively limited somatosensory input but not during tasks characterized by increased somatosenory input. The small magnitude of the improvements, coupled with their apparent lack of carry over to more difficult and functionally relevant tasks, questions the clinical benefit of the present effects of bracing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
80
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 22 publications
1
80
0
4
Order By: Relevance
“…These theories are divided into four categories: hormonal, anatomic, environmental and neuromuscular [11]. Previous studies have shown that knee braces may improve functional performance during tasks such as single limb balance in individuals with ACL injuries [12,13]. Butler et al [14] also showed changes in landing mechanics in patients following ACL reconstruction while wearing a brace.…”
Section: Introductionmentioning
confidence: 99%
“…These theories are divided into four categories: hormonal, anatomic, environmental and neuromuscular [11]. Previous studies have shown that knee braces may improve functional performance during tasks such as single limb balance in individuals with ACL injuries [12,13]. Butler et al [14] also showed changes in landing mechanics in patients following ACL reconstruction while wearing a brace.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the biomechanical effects of knee bracing after 55 ACLR, however knee braces may also improve functional performance during tasks such 56 as single limb balance [17,18] and self-reported knee function in ACLR individuals [19].…”
mentioning
confidence: 99%
“…There is some evidence that supports KB enhancing the single limb balance [17,289 18] but KT has no effect on balance in ACLR individuals [ GRS scores were higher with KB than KT.…”
mentioning
confidence: 99%
“…Although literature reported that compressive sleeves improve knee proprioception and single-limb standing balance in subjects with ACL-reconstruction, but research on the effects of knee brace on dynamic balance is limited (9,10).…”
Section: Introductionmentioning
confidence: 99%